A Conceptual Study of Role of Vyadhikshamatava in Origin and Management of Diseases w.s.r. to Covid-19 (AYUSHDHARA, 2024)
The Ayurvedic approach to healthcare is distinct from the allopathic approach, as it is not primarily focused on using drugs. In Ayurveda, there are numerous drugs derived from plants, animals, and minerals that are believed to enhance the body's Vyadhikshamatava. However, to fully benefit from these substances, they must be used in accordance with the principles of Ayurveda. According to Ayurveda, the emergence of disease is intricately connected to distinct factors collectively referred to as Nidanadi Visheshas. These factors encompass Nidan, Doshas, and Dushyas. The pivotal determinants influencing whether a disease manifests or not lie in the Prativisheshas associated with Nidanadi Visheshas to the dynamic interplay of Vikaarvighaat Bhava-Abhava. Understanding Vikaarvighaat Bhava, Abhava, and Prativisheshas is crucial for assessing pathogenesis, determining the Sadhyasadhyata, and formulating an appropriate treatment protocol. Various principles are advocated for the management of diseases. In this sequence, the desired increase in the best Dhatu Saar and Oja by prior conditioning through the best diet, medicine, Rasaysana, etc. can be adopted along with altering the body through purification therapies such as emesis or purgation. Another approach involves using substances or medicines with properties and actions opposite to those causing the disease, adhering to the general principle of treatment. Additionally, refining the body using substances similar to the factors that could cause the disease is known as Purvaabhisanskaar.